DNA Vaccines Encoding Antigen Targeted to MHC Class II Induce Influenza-Specific CD8+ T Cell Responses, Enabling Faster Resolution of Influenza Disease - Lambert, Laura; Kinnear, Ekaterina; McDonald, Jacqueline U.; Grodeland, Gunnveig; Bogen, Bjarne; Stubsrud, Elisabeth; Lindeberg, Mona M.; Fredriksen, Agnete Brunsvik; Tregoning, John S. (Frontiers in Immunology, 2016)
Current influenza vaccines are effective but imperfect, failing to cover against emerging strains of virus and requiring seasonal administration to protect against new strains. A key step to improving influenza vaccines is to improve our understanding of vaccine induced protection. Whilst it is clear that antibodies play a protective role, vaccine induced CD8+ T cells can improve protection. To further explore the role of CD8+ T cells we used a DNA vaccine that encodes antigen dimerised to an immune cell targeting module. Immunising CB6F1 mice with the DNA vaccine in a heterologous prime boost regime with the seasonal protein vaccine improved the resolution of influenza disease compared to protein alone. This improved disease resolution was dependent on CD8+ T cells. However, DNA vaccine regimes that induced CD8+ T cells alone were not protective and did not boost the protection provided by protein. The MHC targeting module used was an anti-I-Ed single chain antibody specific to the BALB/c strain of mice. To test the role of MHC targeting we compared the response between BALB/c, C57BL/6 mice and an F1 cross of the two strains (CB6F1). BALB/c mice were protected, C57BL/6 were not and the F1 had an intermediate phenotype; showing that the targeting of antigen is important in the response. Based on these findings, and in agreement with other studies using different vaccines, we conclude that in addition to antibody, inducing a protective CD8 response is important in future influenza vaccines.